Effects of an exercise programme on non-insulin dependant diabetes mellitus - N. Mshunqane; D. Cohen; J. K. Kalk (AOSIS, 2004)
Introduction: The best approach in minimising or delaying thecomplications associated with type 2 diabetes mellitus (NIDDM) in South African physiotherapy rehabilitation services has not been established. Physiotherapists continue to rehabilitate amputees as a result of diabetes mellitus. As hospital costs continue to rise every year, it becomes very costly to keep the patients for longerperiods. A study was undertaken at the Bethlehem Regional Hospital in the Free State to determine the effects of supervised and unsupervised exercise programmes in patients with non insulin dependant (type 2) diabetes mellitus. Aim: The purpose of this study was to evaluate the effects of the two different exercise programmes i.e. hospital based and home based exercise programmes on patients with type 2 diabetes mellitus. Methodology: The hospital based programme consisted of supervised walking and cycling whilst the home based programme consisted of walking only. Changes in measures of obesity, exercise capacity, glycaemic control and  plasma lipids were monitored before the exercise programme and 3 months after graded exercise programmes. Results: The exercise programmes significantly improved exercise capacity, anthropometric measurements and blood glucose levels but had no effect on lipid profiles. There was similar improvements in all the groups but no difference was found when comparing the results between the groups. Conclusion: Although there was no significant difference between the groups, it is concluded that, any form of low endurance exercise programme, whether supervised or unsupervised is beneficial for patients with type 2 diabetes mellitus.